FOODLIT-PRO: Developing Food Literacy - Rosas,Raquel (2018)
At the National Action Plan for Food and Nutrition 2015-2020, the WHO highlights that poor dietary habits are responsible for many non-communicable diseases (e.g., diabetes, cardiovascular diseases, some cancers). Given the urgency to improve food intake, the lack of consensus over the concept of food literacy and the need of research in this domain, compromises the improvement of eating habits. To identify theoretical gaps, two conceptual models of food literacy (FL) are confronted and goals to develop FL are presented (construct, measure and intervention development) in the ambit of the project FOODLIT-PRO. The first model defines FL as intertwined food-related knowledge, competencies and behaviours that promote physical and psychological wellbeing, having as domains Planning, Selecting, Preparing, and Eating. The second model characterises FL as a combined set of food-related skills and knowledge that support a daily healthy diet, building resilience and incorporating the domains of Preparation, Organisations, Psycho-social Factors, and Knowledge. The lack of psycho-social variables in the first FL model, which is achieved on the second one, highlights the relevance on research concerning psychological dimensions of FL. Aiming the development of this field, this work presents the protocol for the first stage of FOODLIT-PRO.